2011
DOI: 10.1111/j.1747-4949.2011.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurological Deterioration (END) after Stroke: The END Depends on the Definition

Abstract: Neurological worsening poststroke is a serious clinical condition that occurs in up to one-third of patients. This brief report summarizes several of the current issues faced by neurologists in recognizing and managing patients who experience a worsening neurological status following hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 8 publications
3
125
0
2
Order By: Relevance
“…2 Neurologic deterioration (ND), an event that occurs in about one-third of patients with acute ischemic stroke (AIS) and contributes to morbidity and mortality, 10,11 has no standardized definition. 12 Currently, clinical studies use inconsistent definitions of ND with differing stroke scales in order to quantify clinical worsening over days, [13][14][15][16] weeks, 17 or months 18 ( Table 1). Some definitions of ND might be too narrow 19,20 and may exclude patients whose neurologic function may be recoverable, while other definitions may be too broad 14,21 and could prompt the unnecessary work-up of false-positive episodes of ND.…”
Section: Introductionmentioning
confidence: 99%
“…2 Neurologic deterioration (ND), an event that occurs in about one-third of patients with acute ischemic stroke (AIS) and contributes to morbidity and mortality, 10,11 has no standardized definition. 12 Currently, clinical studies use inconsistent definitions of ND with differing stroke scales in order to quantify clinical worsening over days, [13][14][15][16] weeks, 17 or months 18 ( Table 1). Some definitions of ND might be too narrow 19,20 and may exclude patients whose neurologic function may be recoverable, while other definitions may be too broad 14,21 and could prompt the unnecessary work-up of false-positive episodes of ND.…”
Section: Introductionmentioning
confidence: 99%
“…[2,15,[22][23][24] In our study, the mortality rates on discharge were not different between groups. Although the patients with progressive disease had higher NIHSS scores on admission, it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 57%
“…The definition of ND at our center (2 point deterioration over a 24 hour period) may be more lenient than others. 2 However, as discussed above, we have found that even a 2-point increase in the NIHSS is clinically significant and may lead to disability or even in-hospital death and therefore should not be discounted. As our standard is to perform the NIHSS in order to assess for ND each morning prior to attending rounds, our ability to measure the precise time each ND actually occurred is less granular than desired.…”
Section: Discussionmentioning
confidence: 97%
“…1 While various definitions of neurologic deterioration have been utilized throughout the literature and no consensus has been reached, 2 our center has defined neurologic deterioration as an increase in the National Institutes of Health Stroke Scale (NIHSS) score (stroke severity score, with higher scores representing more severe strokes) by 2 or more points within a 24-hour period during hospitalization. 3 As we and others have shown, even a small worsening in NIHSS (as few as 2 points) has been associated with poorer prognosis when compared to patients who do not deteriorate.…”
Section: Introductionmentioning
confidence: 99%